Preparation of food supplements from oilseed cakes - Sunil, L. (J Food Sci Technol, 2014)
Oilseed cakes have been in use for feed preparation. Being rich in proteins, antioxidants, fibers, vitamins and minerals, oilseed cakes have been considered ideal for food supplementation. These oilseed cakes can be processed and made more palatable and edible by suitable treatments and then incorporated as food supplements for human consumption. Rice bran pellets (RBP), stabilized rice bran (SRB), coconut cake (CC) and sesame cake (SC) were taken up for the study. These were mixed with distilled water and cooked in such a way to separate the cooked solid residue and liquid extract followed by freeze drying to get two products from each. The raw, cooked dried residue and extract were analyzed for various parameters such as moisture (0.9–27.4 %), fat (2.1–16.1 %), ash (3.3–9.0 %), minerals (2.6–633.2 mg/100 g), total dietary fiber (23.2–58.2 %), crude fiber (2.7–10.5 %), protein (3.2–34.0 %), and the fat further analyzed for fatty acid composition, oryzanol (138–258 mg/100 g) and lignan (99–113 mg/100 g) contents and also evaluated sensory evaluation. Nutritional composition of products as affected by cooking was studied. The cooked products (residue and extract) showed changes in nutrients content and composition from that of the starting cakes and raw materials, but retained more nutrients in cooked residue than in the extract. The sensory evaluation of cooked residue and extract showed overall higher acceptability by the panelists than the starting cakes and raw materials. On the basis of these findings it can be concluded that these cooked residue and extract products are highly valuable for food supplementation than the raw ones.